Analisis Efektivitas Pembangunan Gardu Induk New Garuda Sakti Untuk Mengurangi Rugi Daya Saluran Distribusi Primer 20 KV - Rani Sulistiani; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The New Garuda Sakti substation (GI NGS) is a substation that function to reduce electrical power losses at Pekanbaru region. This substation has five feeders of 20 KV which are distribution the load from the previous feeders supplied from three substations. By calculating the amount of power losses, electricity costs, comparison of power losses before and after in the New Garuda Sakti Substation, it can be seen the effectiveness of the substation construction. The total power losses before being supplied from the GI NGS is 201,801.77 W and after being supplied from the GI NGS is 34,251.94 W. Then, the average power losses per month can be reduced by 43,600.05 W and the average savings cost per month is Rp. 26,468,513.33. Thus, the presence of GI NGS is very effective in reducing electricity losses for the Pekanbaru region and saving operational cost for the company.Keywords : The effectiveness of GI NGS, distribution load, power losses, average power losses